To study generation Z presentation about use of AI in creating challenge and opportunities of future jobs in Ahmedabad - Viranchi, Trivedi; Dalvadi, Ankit; Vidani, Dr. Jignesh (Contemporary Journal of Applied Sciences, 2024)
The rapid advancement of artificial intelligence (AI) is significantly changing the global job market, creating challenges and opportunities for future jobs. This study investigates Generation Z’s perceptions of the role of AI in shaping the future of work. Through descriptive data collection, the study examines how AI impacts job opportunities, potential job displacement due to automation, and Generation Z’s readiness to adapt to an AI-driven workforce. The study also explores the readiness of education systems to equip Generation Z with the skills needed to succeed in this evolving job market. By providing insight into how this generation views the evolving job landscape, the study aims to inform educators, policymakers, and employers on how to better support Generation Z in their career development